2021
DOI: 10.1186/s12958-021-00779-0
|View full text |Cite|
|
Sign up to set email alerts
|

OTOGL, a gelforming mucin protein, is nonessential for male germ cell development and spermatogenesis in mice

Abstract: Otogelin-like protein (encoded by Otogl) was highly structural similar to the gelforming mucin proteins. Although human OTOG mutations have been linked to deafness, the biological function of OTOGL in male germ cell development remains enigmatic. In screening 336 patients with non-obstructive azoospermia (NOA), OTOGL displays the high mutant ratio (13.99 %). Then, we examined the expression of OTOGL in developing mouse testes. Otogl mRNA and protein are continually expressed in postnatal developing testes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Serbp1 KO mice were generated and produced by zygote pronuclear microinjection using CRISPR/Cas9 genome editing as our previously described method [ 34 ]. Briefly, 2 single guide RNAs (sgRNAs) (target exon 1 and 3) and Cas9 mRNAs were mixed and injected into C57BL/6 zygotes for generating founder mice.…”
Section: Methodsmentioning
confidence: 99%
“…Serbp1 KO mice were generated and produced by zygote pronuclear microinjection using CRISPR/Cas9 genome editing as our previously described method [ 34 ]. Briefly, 2 single guide RNAs (sgRNAs) (target exon 1 and 3) and Cas9 mRNAs were mixed and injected into C57BL/6 zygotes for generating founder mice.…”
Section: Methodsmentioning
confidence: 99%
“…Adad2 and Rnf17 mutant mice were generated produced by zygote pronuclear microinjection using CRISPR/Cas9 genome editing as previously described ( Li et al, 2021 ). Two single guide RNAs targeting exon 1 and Cas9 mRNAs were mixed and injected into C57BL/6 zygotes, followed by implanted into pseudo-pregnant C57BL/6 females.…”
Section: Methodsmentioning
confidence: 99%
“…https://doi.org/10.1186/s12958-021-00779-0 Following publication of the original article [1], the authors reported an error in Fig. 1.…”
Section: Correction To: Reprod Biol Endocrinol 19 95 (2021)mentioning
confidence: 99%